Buku Teks dan Kurikulum 2013: Meningkatkan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Bahasa Indonesia - Timanta Agustina Br Purba; Enjel Trisnawaty Banjarnahor; Deby Dame Riani Hutauruk; Windrya Anatasya Siahaan; Putri Sion Siallagan; Zakia Ritonga (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to find out the meaning of textbooks and curriculum in improving students' critical thinking in learning Indonesian. This research method uses descriptive qualitative research. Researchers are key instruments for research subjects in Indonesian language textbooks in various curricula. Education is a process or effort carried out by a person. It is with the curriculum that schools can describe and formulate the qualifications and competency outcomes of their educational programs and with the curriculum the school designs efforts to achieve competency.